The Influence of Financial Literacy and Financial Technology on Students’ Financial Behavior - Azifah Syahfitri; Suhardi M. Anwar; A. Antong (Golden Ratio of Finance Management, 2026)
This study aims to examine the influence of financial literacy and financial technology on the financial behavior of students at the University of Muhammadiyah Palopo. Financial technology refers to the use of digital-based financial services, such as e-wallets, mobile banking, and paylater applications. Financial literacy is defined as students’ ability to understand financial concepts, manage budgets, and make prudent financial decisions. This study involved 395 students from the Faculty of Economics and Business in 2022, with 80 respondents selected using the Slovin formula with a 10% margin of error. The data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS. The results indicate that financial literacy has a positive and significant effect on students’ financial behavior, and financial technology also has a positive and significant effect. Other factors outside the research model may influence the remaining variance. The implications of this study highlight the importance of improving students’ financial literacy to encourage the wise use of financial technology. Furthermore, universities are encouraged to provide financial education and digital literacy programs to foster healthier financial behavior among students.